Comentario periodístico de Rafael Cuesta y su influencia en la opinión pública - Vergara Moreira, Rosa Angélica (2021)
The purpose of this project is to analyze whether the journalistic comment by Rafael Cuesta broadcast in "El Noticiero" of TC my channel has influence on public opinion, taking into account that journalistic opinion has a positive background in several important historical events. The modality of this work is investigative, by means of the observation sheet, the time, structure, language and issues considered of relevance are analyzed, generated by an investigation by a journalist. The interview to find out if the journalist in question knows the scope of his criteria in the viewers and the survey to define by the citizens if the value judgment of Cuesta influences them. Once all the investigative techniques had been carried out to analyze and verify whether Rafael Cuesta's journalistic comments really have a certain influence on the criteria of public opinion, it was shown that indeed journalistic opinion programs continue to have an important and significant audience and that the segment under study is observed and influences and guides society in a certain way.